Pharmaco-dynamics of CSA and Tacrolimus and its Effect on Antiviral Drugs in HCV Positive Kidney Transplant Recipients. (July 2018) - Mehrotra, Sonia; Sharma, Raj Kumar; Reddy, Suresh; Prasad, Narayan; Gupta, Amit; Bhadauria, Dharmendra S.; Kaul, Anupama
Abstract : Background: The aims of this pilot study were to assess the effect of interferon free sofosbuvir and ribavirin combination regimen used to treat chronic hepatitis C viral (HCV) infection in kidney transplant recipients on pharmacokinetics of calcineurin inhibitor (CNI ) drugs.Direct acting antiviral drugs can affect drug levels of CNIs by increasing their clearance. Pharmacokinetics of CNI drugs need to be studied while transplant patients are on Sofosbuvir to see effect on AUC as decreased exposure to immunosuppression can precipitate rejection. Methods: Ten patients having chronic HCV infection in kidney transplant recipients were included in the study. All received Sofosbuvir and Ribavirin combination therapy. 400 mg OD plus Ribavirin 400mg BD for 12 wks for Genotype 1, 2 and 4, for 24 wks for Genotype 3. The virological response to therapy was studied. Area under the curve and pharmacokinetic data of levels of CNI were compared while the patients were receiving sofosbuvir and ribavirin drugs to AUC while they were not on these drugs. Results: Nine (9/10) patients achieved rapid virological response (RVR) with undetectable HCV RNA at 4 weeks (90%) and the remaining 1 patient got undetectable HCV RNA at 8 weeks. The sustained virological response (SVR3) at 3 months, at 6 and 12 months (SVR6, SVR12) was seen and maintained in all the 10 patients (100%). The important aspect of the study is the effect of treatment with the sofosbuvir - ribavirin combination regimen on the CNI AUC levels with reduction in CNI AUC resulting in all patients requiring increase in the dose of CNI (tacrolimus and cyclosporine) used as a part of triple drug immunosuppression. AUC for tacrolimus was 108.83 ± 24.29 ng./mL before starting sofosbuvir and ribavirin which decreased to 85.51± 18.25 ng./mL within 7 days of starting the antiviral treatment ( p=0.001). AUC for cyclosporine was 2584.2± 141.7 ng./mL before starting sofosbuvir and ribavirin which decreased to 1409.6±130.5 ng./mL within 7 days of starting the antiviral treatment ( p=0.084). Conclusion: The sofosbuvir and ribavirin combination therapy is very effective to treat HCV infection in post renal transplant setting. There is need of close CNI level monitoring and dose adjustment with sofosbuvir therapy. With sofosbuvir therapy and viral clearance, there could be reduction in CNI levels due to increased clearance of the CNI drugs, which is shown by the AUC measurements. This could be important for patients at high risk for rejection. Our patients did not have any rejection episode; they were all PRA negative with no DSA.